CCAFS Southeast Asia R4D Thrusts, 2019-2021: New outlook towards a food secure future. - Sebastian, Leocadio S.; Bernardo, Eisen Bernard (2018)
The posters discuss the new research outlook of CCAFS regional program in Southeast Asia (SEA). As the program enters its second phase, CCAFS SEA will be working on activities that will help SEA countries to: cope with climate change, sustain national and regional food and nutrition security, enhance competitiveness in agriculture, and strengthen regional integration. The new R4D framework and focus are also showcased in the posters. CCAFS Southeast Asia will converge the activities of its four R4D flagships in the CSVs towards an integrated set of activities and interventions. Descriptions of the new flagship projects that will be implemented in the region are also included in the posters.